Single-Center Experience in Patients with Mixed Gonadal Dysgenesis - Ebru Barsal Çetiner; Zeynep Donbaloğlu; Berna Singin; Bilge Aydın Behram; Kürşat Çetin; Güngör Karagüzel; Hale Tuhan; Mesut Parlak (AVES Yayincilik, 2024)
Objective: Mixed gonadal dysgenesis (MGD) is an uncommon chromosomal Disorder of Sexual Development (DSD). There is insufficient information regarding clinical findings and growth patterns. This study aimed to provide more information about mixed gonadal dysgenesis, which has not yet been sufficiently defined. Materials and Methods: Data from 10 patients diagnosed with mixed gonadal dysgenesis were retrospectively reviewed. Clinical presentations, complaints at admission, imaging, genetic results, and treatments received by the patients were examined. Gonadal status and the gender of the patients were reared and evaluated by a multidisciplinary council decision. If received, growth hormone treatment doses and height gains were examined. Results: The patients' ages at admission range from 6 months to 17.5 years. The median height SDS of the patients was −0.75 (2.73), the mean body weight SDS was −0.49 (±1.46), and the mean body mass index (BMI) SDS was 0.26 (±0.97). The complaints at admission varied, including ambiguous genitalia, short stature, and absence of menstruation. Some patients are completely in the female phenotype, while some are inadequately virilized male phenotype. External Masculinization Score (EMS) ranges from 1 to 6.5. The decision to raise 6 patients as female and 4 patients as male was made by a multidisciplinary council. Growth hormone treatment was administered to patients raised as female and diagnosed with short stature. The height SDS gain in treated patients was 0.42 (±0.49). Conclusion: Due to its rarity and varied clinical presentation, our knowledge about mixed gonadal dysgenesis is limited. Therefore, early diagnosis and individualized treatment plans are crucial for this patient group.